Novel biomineralization strategy in calcareous foraminifera - Borrelli, Chiara; Panieri, Giuliana; Dahl, Trine Merete; Neufeld, Kai (Scientific Reports, 2018)
Source at https://doi.org/10.1038/s41598-018-28400-2 . Licensed CC BY-NC-ND 4.0. This work shows that calcareous benthic foraminifera are capable of agglutinating sedimentary particles also. In particular, we focus on Melonis barleeanus. Traditionally considered a calcareous species, our data revealed the presence of minute (~3 μm) sedimentary particles (silicate grains) inside the chamber walls of the examined shells. These particles were arranged in a definitive and systematic pattern, and the similar grain chemical characterization and size suggested a relatively high degree of selectivity in both modern and fossil specimens. Based on these results, we propose that M. barleeanus is capable of agglutinating sedimentary particles during the formation of a new chamber. The analysis of other calcareous foraminiferal species (e.g., Cassidulina neoteretis, Lobatula lobatula, Nonionella stella) did not reveal the presence of silicate grains in the shell of the specimens analyzed confirming this to be a characteristic of M. barleeanus. Considering that the isotopic and chemical composition of this species is widely used in paleoclimatic and paleoceanographic reconstructions, we used a mixing model to better constrain the influence of sedimentary particles on M. barleeanus δ 18 O data. Our model showed that the calcite δ 18 O would increase by ~0.9–2‰ if 10 wt% of feldspars (i.e., anorthite, albite, orthoclase) and quartz, respectively, were included in the analyzed shell. Based on these results, we emphasize that it is of paramount importance to consider M. barleeanus unusual biomineralization strategy during the interpretation of geological records and to investigate the presence of similar processes in other calcareous foraminiferal species.